Determinants, barriers, and concepts of husband’s involvement in antenatal care among women in Pakistan - Khan, Javeria; Abid, Sidra; Mumtaz, Sarwat (Journal of the Pakistan Medical Association, 2024)
Dear Madam, Antenatal care undoubtedly plays a vital role in improving maternal and child health and ensuring that the maternal mortality ratio, which remains alarmingly high across many countries, including Pakistan, continues to reduce. With males traditionally seen as heads of households and society’s primary breadwinners and often determining the fate of their wives in many households, including them in health decision-making may equally contribute to gender equality and empowerment. However, there is still little research available on the subject. Goal 3.1 of the Sustainable Development Goals is to reduce the global maternal mortality ratio to less than 70 per 100,000 live births by 2030. In Pakistan, therefore, the promotive factors of male participation in antenatal care are necessary for ensuring low maternal and child mortality and contributing to gender empowerment. Active participation of men in prenatal care outcomes into essential improvement in pregnancy and preparing parents with knowledge of maternal morbidity and mortality (1). Although contributing dimensions include cultural, socio-economic, and health-related factors, maternal and infantile health continues to be a problem in Pakistan. The inability to access care services, particularly in remote rural areas, financial disparities, and traditional perceptions act as obstacles to comprehensive ANC (2). However, recent patterns indicate an improvement in ANC utilization and a growing understanding of male adjuncts (3). Nevertheless, despite these changing trends, a critical knowledge gap on the trends, determinants, barriers, and policy influences on male ANC involvement persists in Pakistan. Although maternal mortality rates have shown a steady decrease over the last few years, they remain high, indicating low levels of ANC utilization and involvement (4). Socioeconomic disparities, including poverty, lack of education, and limited economic opportunities, exacerbate the situation, as these factors hit vulnerable communities the hardest. Furthermore, cultural factors continue to be influential in determining whether a woman seeks antenatal and the quality of the perinatal care she receives. Nevertheless, in the last few years, the situation has begun to change, with a positive upward trend in the utilization of antenatal services and the recognition of male involvement in ANC (5). Greater male engagement during antenatal care has been viewed from a hopeful lens, a gap such as the complete understanding remains. There have been limited studies on the participation of men in antenatal care in Pakistan. Therefore, to the best of our knowledge, the present study is conducted to develop an understanding of emerging patterns. ---Continue